The physical activities of generation z and the use of digital technologies in the training of boxing students - Kogan O.S.; Yamileva R.M.; Bresler M.G.; Greb A.V. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to discern the unique characteristics of Generation Z students’ preferences in sports at the university, and to assess the impact of incorporating innovative technologies into the training process for boxing students. Methods and structure of the study. The study examines the prevalence of esports and digital sports among students at Ufa State Petroleum Technical University (USPTU). The study compares the effectiveness of training athletes in boxing using innovative technologies (digital sports) with a control group of athletes who use traditional methods. The study measures the performance of athletes in the tapping test, sensorimotor reaction time, and the correction test. Results and conclusions. Based on the research and analysis of USPTU students’ perspectives, it is evident that competitions in digital disciplines, which incorporate the use of cutting-edge technologies in e-sports, robotics, IT, and AI, are gaining popularity among young people. The integration of digital sports technology into the training regimen of boxers in AFP classes has been shown to enhance their reaction time and focus, resulting in improved performance.